Bralna pismenost v predšolski vzgoji in izobraževanju (University of Maribor Press, 2017)
Reading Literacy in the Pre-school Education. Scientific monograph Reading literacy in the pre-school education is the result coming at the end of the research-development project Hugged by words. The project was supported by the Ministry of culture of RS (October 2016 – October 2017). The theme of the project is support and encouragement of family reading and family literacy, which included intergenerrational reading in all areas of kindergarten activities and in all areas of child development. The monograph includes fifteen chapters: the model of family literacy and evaluation of this project, this is followed by chapters on child’s linguistic development, easy-to-read materials, information, visual literacy and development of linguistic sensitiveness in various curricular areas. The monograph is the result of studies and adaptations coming from the research part of the project, and as such presents some solutions and improvements in the area of family reading. It also demonstrates the collaborative interdisciplinary nature of relationships between different disciplines, also placing special emphasis on the special needs groups. Reading literacy transcends intergenerrationally, and is a set of competences which develop through the entire life.